REKONSTRUKSI PEMAHAMAN HUKUM ISLAM TERHADAP PERNIKAHAN BEDA AGAMA: KAJIAN KRITIS ATAS KHI DAN FATWA MUI - Jannah, Roikhatul; Nurcahyo, Satria Avianda (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the juridical-sociological review of the Compilation of Islamic Law (KHI) and ulama fatwas related to interfaith marriages in Indonesia. The method used is qualitative with a descriptive-analytical approach, combining legal document review and in-depth interviews with scholars, legal practitioners, and couples involved in interfaith marriages. Primary data were obtained from MUI fatwas, related articles in the KHI, and interviews with relevant informants. Secondary data were collected from related literature, legal journals, and previous research results. This study found that the KHI, which is the main guideline in Islamic family law in Indonesia, strictly prohibits interfaith marriages, as regulated in Article 40 letter c and Article 44 of the KHI. MUI Fatwa Number 4 of 2005 emphasizes the impermissibility of marriage between Muslims and non-Muslims, on the grounds of maintaining the sanctity of Islamic teachings. However, from a sociological perspective, the study shows that there are various challenges and social dynamics that influence the practice of interfaith marriages. Interviews with informants indicate that factors such as social policies, family pressure, and personal commitment are the main considerations in deciding on interfaith marriages. This study concludes that the development of laws and fatwas of ulama need to consider aspects of humanity and social diversity, in order to create a balance between adherence to religious teachings and the needs of an increasingly pluralistic society. The recommendations of this study include the importance of interfaith dialogue and the improvement of the KHI to include more inclusive guidelines in dealing with the dynamics of interfaith marriage in Indonesia.